Optimization of Stiffness and Damping for Multi-storey Structures. (2016) - Ambetkar, Vighnesh; Ahmed, Abbas; Kumar, Deepak
Abstract: Efficiency of structural control for dynamic systems is highly dependent on the frequency contents of the excitation and structural frequency. For a given excitation, structural response control can be achieved by optimizing the stiffness and damping of the structure. The structural storey stiffness can be reduced using negative stiffness devices, while damping can be increased by using viscous dampers. A five-storey structure is considered in which stiffness and damping for every storey is optimized for minimum response. It is seen that for the response control, in some cases, storey stiffness is optimized for lesser value than the original storey stiffness. The results indicate that considerable structural control can be achieved for initially soft structures, whereas for very stiff structures, the optimization technique is ineffective.